Translated by Ibn Awad Jr. with part of the manuscript - Wissam Abdul Hamid Abdullah (Islamic Sciences Journal, 2024)
ABSTRACT This research is drawn from the thesis titled: Al-Rawd al-Anis ala Kubra al-Sanussi, by Imam Ahmad ibn Ahmad ibn Muhammad ibn Awad al-Maqdisi (died after 1183 AH), which invited us to choose this research - to study and investigate - its connection to the science of monotheism and attributes, which is called the science of theology, and the book The Creed of the People of Monotheism, by Imam Abu Abdullah Muhammad bin Yusuf al-Senussi (d. 895 AH), is a solid text that has been accepted by scholars and students of knowledge with explanations and footnotes. In this research, we briefly defined the personal and scientific biography of the author Ibn Awad (the son), the author of the commentary, and then followed it with a part. Study and investigation of the manuscript.